Local Wisdom in Traditional Medicine: Documentation of Medicinal Plants and Utilization by the Forest Community of Tangkahen Village - Indrayanti L; Nuwa; Santoso M; Dwiastuti R; Afentina; Sinaga YR; Yanarita; Grace Siska (Jurnal Penelitian Pendidikan IPA, 2025)
Rural communities often rely on medicinal plants for primary healthcare; however, thier knowledge of the diversity and use of these plants is not well documented. This study aims to identify medicinal plant species, their modes of use, and to support the preservation of local cultural wisdom. The research is conducted in the Tangkahen Village Forest, Central Kalimantan, using a 100% exploratory inventory method. Observations are made along three transects representing dense, moderate, and sparse forest cover. Information on plant utilization were obtained through interviews with local traditional healers. This study found 108 individual medicinal plants, representing 16 species from 13 botanical families. The most represented families are Orchidaceae (19%) and Auriculariaceae (13%), with others such as Araceae, Lauraceae, Apocynaceae, and Fabaceae comprising smaller percentages. These plants are used to treat 22 types of ailments, including diabetes, cancer, cardiovascular disease, digestive disorders, and for cosmetic purposes. Preparation methods includes decoction, infusion, topical application of pounded material, and direct consumption. The most commonly used plant parts are leaves, stems, roots, sap, and bark. Some involves combination of 2–3 species. The availability of these plants supports local health needs and presents opportunities for economic development through further processing, thereby indirectly contributing to food security. Further pharmacological studies are needed to analyze their compounds. Cultivation efforts are also essential to ensure the long-term sustainability of these medicinal resources.